Penguatan Kapasitas Masyarakat melalui Pelatihan Energi Surya dan Sistem Informasi Desa pada Program SERASI - Yan Aditiya Pratama; Hovi Herawadi Sudibyo; Sri Lestari (Penerbit Goodwood, 2026)
Purpose: This community service study aims to enhance community capacity in managing eco-tourism and local economic activities through training-based technology adoption under the SERASI program in Desa Sidodadi. Research Methodology: The program was implemented in Desa Sidodadi, Pesawaran Regency, Indonesia, using a Participatory Action Research (PAR). Activities included socialization, training, mentoring, and evaluation. The main tools applied were Smart Eco-Lighting systems based on solar energy, a Village Information System website with an MSMEs e-catalog, and digital promotion platforms. Results: The results indicate improved community knowledge and practical skills in renewable energy utilization and digital management. Participants were able to operate and maintain Smart Eco-Lighting, manage village website content, and use digital media to promote eco-tourism and MSMEs products. The establishment of a local management team reflects increased community readiness and ownership. Conclusions: The results indicate that training-based community empowerment effectively supports sustainable eco-tourism and digital village development by strengthening technical, institutional, and human resource capacity, while fostering community participation, ownership, and long-term sustainability. Limitations: This study is limited by focusing on one village. Thus, it may affect the generalizability of the results to other contexts. Contributions: This study proposes a practical model for community-based training that integrates renewable energy and digital technology to support sustainable rural tourism and local economic development.